Expanding the clinical spectrum associated with PACS2 mutations. Issue 4 (28th February 2019) - Dentici, Maria L.; Barresi, Sabina; Niceta, Marcello; Ciolfi, Andrea; Trivisano, Marina; Bartuli, Andrea; Digilio, Maria C.; Specchio, Nicola; Dallapiccola, Bruno; Tartaglia, Marco
Abstract : Whole exome sequencing (WES) has led to the understanding of the molecular events affecting neurodevelopment in an extremely diverse clinical context, including diseases with intellectual disability (ID) associated with variable central nervous system (CNS) malformations, and developmental and epileptic encephalopathies (DEEs). Recently, PACS2 mutations have been causally linked to a DEE with cerebellar dysgenesis and facial dysmorphism. All known patients presented with a recurrent de novo missense mutation, c.625G>A (p.Glu209Lys). Here, we report on a 7‐year‐old boy with DEE, cerebellar dysgenesis, facial dysmorphism and postnatal growth delay, apparently not fitting with any recognized disorder. WES disclosed a de novo novel missense PACS2 variant, c.631G>A (p.Glu211Lys), as the molecular cause of this complex phenotype. We provide a detailed clinical characterization of this patient, and analyse the available clinical data of individuals with PACS2 mutations to delineate more accurately the clinical spectrum associated with this recently described syndrome. Our study expands the clinical and molecular spectrum of PACS2 mutations. Overview of the available clinical data allow to delineate the condition associated with PACS2 mutations as a variable trait, in which the key features are represented by moderate to severe ID, cerebellar dysgenesis and other CNS malformations, reduced growth, and facial dysmorphism. Abstract : Report on a 7‐year‐old boy with developmental and epileptic encephalopathies, cerebellar dysgenesis, facial dysmorphism and postnatal growth delay with a novel de nova mutation in PACS2 .